Exploring Knowledge, Attitudes and Practices toward Diabetes in Rural Communities in Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Diabetes has been considered globally as a paradigmatic chronic disease, affecting millions of people of all ages. It is an emerging chronic disease that significantly impacts patients' quality of life.Objective: To assess the levels of knowledge, attitudes and practices on diabetes mellitus among rural residents of Sylhet, Bangladesh.Methods: A hospital-based cross-sectional study was directed among the conveniently selected 183 out-patients aged ≥18 years who were clinically diagnosed with diabetes mellitus and interviewed through a pre-tested semi-structured questionnaire in the purposively selected hospital named Moulvibazar 250 Bed District Sadar Hospital, Sylhet, Bangladesh.Results: The mean knowledge score was 4.3±2.2, attitude was 4.0±1.6 and practices were 1.8±1.8. Most rural individuals had poor knowledge (53.6%), average attitudes (54.6%) and poor practices (63.4%) on DM. The knowledge scores were statistically significant with the attitude and practice scores (P